A new species of antbird (Passeriformes: Thamnophilidae) from the Cordillera Azul, San Martín, Peru. (28th January 2017) - Moncrieff, Andre E.; Johnson, Oscar; Lane, Daniel F.; Beck, Josh R.; Angulo, Fernando; Fagan, Jesse
Abstract: We describe a distinctive new species of antbird (Passeriformes: Thamnophilidae) from humid montane forest (1, 340–1, 670 m above sea level) of the Cordillera Azul, San Martín Region, Peru. Plumage, voice, and molecular evidence distinguish this species from its sister taxon Myrmoderus ferrugineus (Ferruginous-backed Antbird), which is found in lowland Amazonian rainforests of the Guiana Shield and Madeira-Tapajós interfluvium. The new species is presently known only from one ridge in the Cordillera Azul, and therefore we recommend further fieldwork to better estimate its distribution and population size.